Charting the Diversity of Strategic Processes in Visuospatial Short-Term Memory. (March 2021) - Gonthier, Corentin
Despite the abundant literature on visuospatial short-term memory, researchers have devoted little attention to strategic processes: What procedures do subjects implement to memorize visuospatial material? Evidence for various strategies exists, but it is spread across a variety of fields. This integrative review of the literature brings together scattered evidence to provide an overview of strategic processes in visuospatial memory tasks. The diversity of strategies and their proposed operating mechanisms are reviewed and discussed. The evidence leads to proposing seven broad strategic processes used in visuospatial short-term memory, each with multiple variants. Strategies can vary across individuals, but the same subjects also appear to use multiple strategies depending on the perceptual features of to-be-remembered displays. These results point to a view of visuospatial strategies as a functional library of facilitatory processes on which subjects can draw to support visuospatial short-term memory performance. Implications are discussed for the difference between visual and spatial tasks, for the appropriate measurement of strategic behaviors, and for the interpretation of performance in visuospatial memory tasks.